1996
DOI: 10.1084/jem.183.4.1937
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the GRB2-associated phosphoprotein SLP-76 in T cell receptor-mediated interleukin 2 production.

Abstract: SummaryRecently we described the molecular cloning of SLP-76, a hematopoietic cell-specific 76-kD protein that was first identified through its association with GST/Grb2 fusion proteins. The primary sequence of SLP-76 predicts a protein of 533 amino acids comprising an amino-terminal region with numerous potential tyrosine phosphorylation sites, a central region rich in proline residues, and a single carboxy-terminal SH2 domain. Here we demonstrate formally that Grb2 associates with unphosphorylated SLP-76 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 30 publications
9
127
0
Order By: Relevance
“…In keeping with this finding, a recent study shows that Vav-1 interacts with linker for activation of T cells in a fashion that depends on phosphorylation by Itk (59), and we have recently found that Itk-deficient cells, like the SLP-76 mutants, are defective in Vav recruitment and localized Cdc42 activation. 4 Although SLP-76 has been shown to bind both Grb2 and Nck (13,60,61), we find that only Nck participates in WASP recruitment. Our results showing that the third SH3 domain of Nck is required for WASP recruitment are consistent with a previous study showing that this SH3 domain binds to the proline-rich domain of WASP in vitro (26).…”
Section: Discussionmentioning
confidence: 63%
“…In keeping with this finding, a recent study shows that Vav-1 interacts with linker for activation of T cells in a fashion that depends on phosphorylation by Itk (59), and we have recently found that Itk-deficient cells, like the SLP-76 mutants, are defective in Vav recruitment and localized Cdc42 activation. 4 Although SLP-76 has been shown to bind both Grb2 and Nck (13,60,61), we find that only Nck participates in WASP recruitment. Our results showing that the third SH3 domain of Nck is required for WASP recruitment are consistent with a previous study showing that this SH3 domain binds to the proline-rich domain of WASP in vitro (26).…”
Section: Discussionmentioning
confidence: 63%
“…WEHI-231 cells were transfected with flag-tagged WT or mutant forms of SLP-76 and immunoprecipitated SLP-76 was subjected to anti-CD22 immunoblotting. The following four mutants were used: SLP-76DN, SLP-76 lacking the minimal prolinerich region required for Grb2/Gads binding (SLP76DPro) [39], SLP-76 lacking the SH2 domain (SLP-76DSH2), and SLP-76 lacking both proline-rich region and the SH2 domain (SLP-76DProDSH2). Although the amount of all exogenously introduced SLP-76 mutants was comparable (Fig.…”
Section: Slp-76 Forms Complex With Gads and Binds Cd22 Via The Sh2 Domentioning
confidence: 99%
“…To this aim, we tested ZAP-70 and the adapter protein SLP-76, two key elements required for NF-AT-induced transcriptional activation (48). Similarly to Vav-1, both proteins are tyrosine phosphorylated following TCR ligation (49,50) and when overexpressed in Jurkat cells they cause an increase of basal (40,42) and Fig. 1, A and B, and Fig.…”
Section: Zap-70 or Slp-76 Overexpression Does Not Induce Nf-at Activamentioning
confidence: 99%